Answer:
Y-int: (0,3)
X-int: (4,0)
Equation: y = -3/4x + 3
Step-by-step explanation:
Answer:
???
Step-by-step explanation:
<span>Simplifying
4x + 20 = 6x + -10
Reorder the terms:
20 + 4x = 6x + -10
Reorder the terms:
20 + 4x = -10 + 6x
Solving
20 + 4x = -10 + 6x
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
20 + 4x + -6x = -10 + 6x + -6x
Combine like terms: 4x + -6x = -2x
20 + -2x = -10 + 6x + -6x
Combine like terms: 6x + -6x = 0
20 + -2x = -10 + 0
20 + -2x = -10
Add '-20' to each side of the equation.
20 + -20 + -2x = -10 + -20
Combine like terms: 20 + -20 = 0
0 + -2x = -10 + -20
-2x = -10 + -20
Combine like terms: -10 + -20 = -30
-2x = -30
Divide each side by '-2'.
x = 15
Simplifying
x = 15</span>
Selection B is appropriate.
_____
The signs of the coefficients tell you the binomial factors must have both signs positive (selections B and C only). Selection B produces an x-term that is 15x+15x=30x (as we want); selection C produces an x-term that is 45x+5x=50x (not what we want).

bear in mind that it goes with the "degree" of the polynomial.